Lithium-sulfur battery positive electrode composite current collector and preparation method and application thereof

By electroplating hydrogen-molybdenum bronze plating on the positive electrode current collector of lithium-sulfur battery, the problem of shuttle effect in lithium-sulfur battery is solved, the cycle performance and capacity of the battery is significantly improved, and the battery life is extended.

CN119275296APending Publication Date: 2025-01-07SICHUAN CHENGKEGUO RENEWABLE ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411693120.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The cycle life of lithium-sulfur batteries is limited by the parasitic reaction (shuttle effect) between lithium polysulfide and lithium metal anode, resulting in a decrease in battery capacity. It is difficult for the existing technology to effectively suppress this problem.

Method used

The hydrogen-molybdenum bronze plating is used to electroplate hydrogen-molybdenum bronze to the surface of the positive electrode current collector of lithium-sulfur battery. The high conductivity of hydrogen-molybdenum bronze and its adsorption ability to suppress the shuttle effect of polysulfides and accelerate its redox kinetics. .

Benefits of technology

The circulation performance and charging and discharge capacity of lithium-sulfur batteries have been significantly improved, the service life of the battery has been extended, and the capacity of lithium-sulfur batteries that have not been modified has been increased by nearly 2 times.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119275296A_ABST
    Figure CN119275296A_ABST
Patent Text Reader

Abstract

The invention provides a lithium-sulfur battery positive electrode composite current collector and a preparation method and application thereof, and belongs to the technical field of lithium-sulfur battery positive electrode current collectors. The positive electrode composite current collector comprises a positive electrode current collector and a hydrogen molybdenum bronze coating attached to the surface of the positive electrode current collector, the hydrogen molybdenum bronze coating is electroplated on the surface of the positive electrode current collector by adopting a cyclic voltammetry method, so that the problems of shuttle effect and slow redox kinetics of polysulfide generally existing in the lithium-sulfur battery are solved. After 400 cycles, the capacity of a lithium-sulfur battery prepared on the basis of the prepared positive electrode composite current collector material is increased by nearly two times compared with that of a conventional lithium-sulfur battery without any modification treatment, and the lithium-sulfur battery has more excellent cycle performance and higher charge-discharge specific capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of positive electrode current collectors for lithium-sulfur batteries, and in particular relates to a positive electrode composite current collector for lithium-sulfur batteries, a preparation method thereof, and an application thereof. Background Art

[0002] Lithium-sulfur batteries have a high theoretical energy density (2600Wh kg -1 ) and environmental friendliness and are considered to be the most promising next-generation rechargeable batteries. However, compared with commercial lithium-ion batteries, current lithium-sulfur batteries still face many challenges due to their limited cycle life, which seriously restricts the practical application of lithium-sulfur batteries. The cycle life of lithium-sulfur batteries is severely limited by the parasitic reaction between lithium polysulfide and lithium metal anode, namely the shuttle effect. Lithium polysulfide, as an inherent intermediate, dissolves in the electrolyte and diffuses to the anode side during charging and discharging to react irreversibly with the negative electrode lithium, resulting in the loss of active materials and a decrease in battery capacity. These problems have greatly limited the application of lithium-sulfur batteries.

[0003] Researchers can effectively alleviate the shuttle effect through structural confinement design, conductive composite material preparation, and interlayer configuration. However, although these methods have achieved certain results in suppressing the shuttle effect, they are all faced with limitations in terms of cost, manufacturing difficulty, energy density, and long-term cycle stability. Accelerating the conversion of LiPS by improving the electrocatalytic activity of the host, rather than preventing the dissolution of LiPS, is another promising strategy to alleviate the LiPS shuttle process. Recently, Al Salem et al. reported pioneering work revealing that Au and Pt can promote reaction kinetics and alleviate LiPS shuttle. Recent reports also show that NbN, MoS2, WS2, WS2-WO3, and TiO2-TiN heterostructures can accelerate the LiPS redox reaction kinetics, thereby stabilizing the polysulfide shuttle process.

[0004] Hydrogen molybdenum bronze (HxMoO3) is a typical molybdenum-based hydroxide semiconductor material. Compared with traditional materials, it has higher conductivity and excellent adsorption capacity for polysulfides, showing broad application potential in lithium-sulfur batteries. However, hydrogen molybdenum bronze is currently mainly used in the fields of catalysis and fuel cells, usually by attaching to metal substrates or mixing with micro-nano materials, and these application forms are significantly different from the needs of lithium-sulfur batteries.

[0005] Therefore, it is very necessary to combine hydrogen-molybdenum-bronze with the treatment of the positive electrode current collector of the lithium-sulfur battery so that the lithium-sulfur battery prepared based on the modified positive electrode current collector can better suppress the shuttle effect. Summary of the invention

[0006] In view of the problems existing in the background technology, the purpose of the present invention is to provide a positive electrode composite current collector for lithium-sulfur batteries and a preparation method and application thereof. The positive electrode composite current collector comprises a positive electrode current collector and a hydrogen-molybdenum-bronze coating attached to the surface of the positive electrode current collector; the hydrogen-molybdenum-bronze coating is electroplated on the surface of the positive electrode current collector by cyclic voltammetry, solving the problems of the "shuttle effect" and the slow redox kinetics of polysulfides commonly existing in lithium-sulfur batteries.

[0007] To achieve the above object, the technical solution of the present invention is as follows:

[0008] A lithium-sulfur battery positive electrode composite current collector comprises a positive electrode current collector and a hydrogen-molybdenum-bronze coating attached to the surface of the positive electrode current collector; the hydrogen-molybdenum-bronze coating is electroplated on the surface of the positive electrode current collector by cyclic voltammetry.

[0009] Furthermore, the positive electrode current collector is a hydrophilic current collector, and the hydrophilic current collector is hydrophilic carbon paper or hydrophilic carbon cloth.

[0010] A method for preparing a lithium-sulfur battery positive electrode composite current collector comprises the following steps:

[0011] Step 1. Cleaning the positive electrode current collector and then drying it;

[0012] Step 2. Prepare hydrogen molybdenum bronze electroplating solution: Add ammonium molybdate ((NH4)6Mo7O 24 ) is dissolved in deionized water and stirred to obtain an ammonium molybdate solution; then concentrated sulfuric acid is added dropwise to the ammonium molybdate solution to adjust the pH value of the solution and stir for a period of time to obtain a hydrogen-molybdenum bronze electroplating solution;

[0013] Step 3. Electroplating hydrogen molybdenum bronze, specifically:

[0014] Using an electrochemical workstation three-electrode system, the positive electrode current collector dried in step 1 was used as the working electrode, Pt was used as the counter electrode, and the calomel electrode was used as the reference electrode. Hydrogen molybdenum bronze was electroplated on the positive electrode current collector by cyclic voltammetry at room temperature;

[0015] Step 4. After the electroplating is completed, the positive electrode current collector is taken out, cleaned and dried to obtain the desired lithium-sulfur battery positive electrode composite current collector.

[0016] Furthermore, in step 1, the positive electrode current collector is a hydrophilic current collector, and the hydrophilic current collector is hydrophilic carbon paper or hydrophilic carbon cloth.

[0017] Furthermore, the hydrophilic current collector is a hydrophilic current collector or a hydrophobic current collector obtained after being subjected to a hydrophilic treatment.

[0018] Furthermore, the specific process of hydrophilic treatment of the hydrophobic current collector is as follows:

[0019] The hydrophobic current collector is firstly ultrasonically cleaned and dried, and then immersed in nitric acid for hydrophilic treatment; after the hydrophilic treatment, it is ultrasonically cleaned and dried again.

[0020] Furthermore, the concentration of ammonium molybdate in deionized water is 0.05-1 mmol / L.

[0021] Furthermore, the pH value of the solution after the concentrated sulfuric acid is added is 2.7-3.

[0022] Furthermore, the specific parameters of the cyclic voltammetry method are: the high voltage is 1V, the low voltage is -1V, the starting voltage is the open circuit voltage, the scanning rate does not exceed 0.05V / S, and the scanning time is 200S-600S.

[0023] The present invention also provides an application of the above-mentioned lithium-sulfur battery positive electrode composite current collector in a lithium-sulfur battery, specifically: sulfur is loaded on the positive electrode composite current collector to obtain a sulfur positive electrode, and a negative electrode shell, a lithium sheet, an electrolyte, a diaphragm, an electrolyte, a sulfur positive electrode, a stainless steel sheet, a spring and a positive electrode shell are placed in sequence from bottom to top, and finally the stacked batteries are sealed with a hydraulic sealing machine to obtain the desired lithium-sulfur battery.

[0024] The mechanism of the present invention is that the surface of the carbon paper or carbon cloth used for the positive electrode current collector of the lithium-sulfur battery is rougher than the metal surface, and the coating is easy to fall off thereon. The present invention adopts cyclic voltammetry for electroplating and sets specific parameters so that the prepared hydrogen-molybdenum bronze coating has good bonding force with the positive electrode current collector and is not easy to fall off.

[0025] In addition, the hydrogen-molybdenum bronze coating has high conductivity and a strong adsorption effect on polysulfides. The multivalent Mo ions in the hydrogen-molybdenum bronze can promote the conversion of polysulfides and have a good promoting effect on the nucleation of Li2S. On the one hand, it inhibits the shuttling of polysulfides, and on the other hand, it accelerates the redox kinetics of S, thereby reducing the existence time of polysulfides to improve the utilization of S.

[0026] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0027] After 400 cycles, the capacity of the lithium-sulfur battery prepared based on the positive electrode composite current collector material prepared by the present invention is nearly 2 times higher than that of the conventional lithium-sulfur battery without any modification treatment, and has better cycle performance and higher charge-discharge specific capacity. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 This is a SEM image of the positive electrode composite current collector carbon paper@hydrogen molybdenum bronze of the present invention.

[0029] Figure 2 This is the EDS diagram of the Mo element in the positive electrode composite current collector material of the present invention.

[0030] Figure 3 This is a long cycle diagram of the lithium-sulfur battery obtained in Example 1 of the present invention at a rate of 0.5C.

[0031] Figure 4 This is the long cycle diagram of the lithium-sulfur battery obtained in Comparative Example 1 at a rate of 0.5C.

[0032] Figure 5 This is a long cycle diagram of the lithium-sulfur battery obtained in Example 2 of the present invention at a rate of 0.5C.

[0033] Figure 6 This is the EDS graph of the Mo element in the composite current collector material obtained in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0034] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention is further described in detail below in conjunction with the implementation modes and the accompanying drawings.

[0035] A lithium-sulfur battery positive electrode composite current collector comprises a positive electrode current collector and a hydrogen-molybdenum-bronze coating attached to the surface of the positive electrode current collector; the positive electrode current collector is a hydrophilic current collector, specifically hydrophilic carbon paper or hydrophilic carbon cloth; the hydrogen-molybdenum-bronze coating is electroplated onto the surface of the positive electrode current collector by cyclic voltammetry; the coating thickness is controlled by controlling the electroplating time.

[0036] The SEM image of the positive electrode composite current collector carbon paper@hydrogen molybdenum bronze is shown in Figure 1 As shown in the figure, it can be seen that the carbon paper is in a fibrous shape, and the hydrogen-molybdenum bronze is electroplated on the surface of the carbon fiber in a wrapped shape. It can be seen that each carbon fiber surface has a core-shell structure. The EDS image of the Mo element in the positive electrode composite current collector material is shown in Figure 2 As shown, from Figure 2 It can be seen that the Mo element can be evenly distributed on the carbon paper, which shows that hydrogen-molybdenum bronze has been successfully electroplated on the carbon paper.

[0037] Example 1

[0038] A method for preparing a lithium-sulfur battery positive electrode composite current collector comprises the following steps:

[0039] Step 1. Select hydrophilic carbon paper and pre-treat it: Use scissors to cut the hydrophilic carbon paper into squares (2×2cm 2 ), then ultrasonically cleaned with alcohol and deionized water for 20 min respectively to remove surface oil and dust, and then placed in a drying oven at 60 ° C for 12 h;

[0040] Step 2. Prepare hydrogen molybdenum bronze electroplating solution: 196 mg of ammonium molybdate ((NH4)6Mo7O 24) was dissolved in 200 mL of deionized water and stirred for 2 h to obtain an ammonium molybdate solution; concentrated sulfuric acid (H2SO4) was slowly added dropwise to the ammonium molybdate solution, the pH value of the solution was adjusted to 3, and stirred for 30 min to obtain a hydrogen-molybdenum bronze electroplating solution;

[0041] Step 3. Electroplating hydrogen molybdenum bronze, specifically:

[0042] Take 30 ml of the hydrogen molybdenum bronze electroplating solution obtained in step 2 into a 50 ml electrolytic cell, use the carbon paper pretreated in step 1 as the working electrode, and a Pt sheet (2×2 cm 2 ) was used as the counter electrode, and the calomel electrode was used as the reference electrode. The electrodeposition was carried out by cyclic voltammetry at room temperature using a CHI660 electrochemical station with a standard three-electrode structure; the working parameters of the cyclic voltammetry were as follows: the high voltage was 1 V, the low voltage was -1 V, the starting voltage was the open circuit voltage, the scan rate was 0.01 V / S, and the scan time was 600 S;

[0043] Step 4. After the electroplating is completed, take out the carbon paper, rinse it with deionized water for 1 minute, and then put it into a drying oven at 60°C for 12 hours to obtain the required lithium-sulfur battery positive electrode composite current collector.

[0044] Example 2

[0045] A method for preparing a lithium-sulfur battery positive electrode composite current collector comprises the following steps:

[0046] Step 1. Select hydrophobic carbon paper and pre-treat it: Use scissors to cut the hydrophilic carbon paper into squares (2*2cm2), then ultrasonically clean it with alcohol and deionized water for 20 minutes respectively to remove surface oil and dust, and then soak the carbon paper in concentrated nitric acid for 12 hours for hydrophilic treatment (the electroplating solution is an aqueous solution. If a hydrophobic material is used, the electroplating will be uneven and difficult to electroplate). Take it out and ultrasonically clean it with deionized water for 20 minutes. Repeat twice to remove the nitric acid residue. After cleaning, put it in a drying oven at 60°C for 12 hours;

[0047] Step 2. Prepare hydrogen molybdenum bronze electroplating solution: 196 mg of ammonium molybdate ((NH4)6Mo7O 24 ) was dissolved in 200 mL of deionized water and stirred for 2 h to obtain an ammonium molybdate solution; concentrated sulfuric acid (H2SO4) was slowly added dropwise to the ammonium molybdate solution, the pH value of the solution was adjusted to 3, and stirred for 30 min to obtain a hydrogen-molybdenum bronze electroplating solution;

[0048] Step 3. Electroplating hydrogen molybdenum bronze, specifically:

[0049] Take 30 ml of the hydrogen molybdenum bronze electroplating solution obtained in step 2 into a 50 ml electrolytic cell, use the carbon paper pretreated in step 1 as the working electrode, and a Pt sheet (2×2 cm 2) was used as the counter electrode and the calomel electrode as the reference electrode, and the electrodeposition was carried out by cyclic voltammetry at room temperature using a CHI660 electrochemical station with a standard three-electrode structure; the working parameters of the cyclic voltammetry were as follows: the high voltage was 1 V, the low voltage was -1 V, the starting voltage was the open circuit voltage, the scan rate was 0.04 V / S, and the scan time was 200 S;

[0050] Step 4. After the electroplating is completed, take out the carbon paper, rinse it with deionized water for 1 minute, put it into a drying oven at 140°C for 12 hours, and then obtain the required lithium-sulfur battery positive electrode composite current collector.

[0051] Example 3

[0052] A method for preparing a lithium-sulfur battery positive electrode composite current collector comprises the following steps:

[0053] Step 1. Select hydrophilic carbon paper and pre-treat it: Use scissors to cut the hydrophilic carbon paper into squares (2×2cm 2 ), then ultrasonically cleaned with alcohol and deionized water for 20 min respectively to remove surface oil and dust, and then placed in a drying oven at 60 ° C for 12 h;

[0054] Step 2. Prepare hydrogen molybdenum bronze electroplating solution: 196 mg of ammonium molybdate ((NH4)6Mo7O 24 ) was dissolved in 100 mL of deionized water and stirred for 2 h to obtain an ammonium molybdate solution; concentrated sulfuric acid (H2SO4) was slowly added dropwise to the ammonium molybdate solution, the pH value of the solution was adjusted to 3, and stirred for 30 min to obtain a hydrogen-molybdenum bronze electroplating solution;

[0055] Step 3. Electroplating hydrogen molybdenum bronze, specifically:

[0056] Take 30 ml of the hydrogen molybdenum bronze electroplating solution obtained in step 2 into a 50 ml electrolytic cell, use the carbon paper pretreated in step 1 as the working electrode, and a Pt sheet (2×2 cm 2 ) was used as the counter electrode, and the calomel electrode was used as the reference electrode. The electrodeposition was carried out by cyclic voltammetry at room temperature using a CHI660 electrochemical station with a standard three-electrode structure; the working parameters of the cyclic voltammetry were as follows: the high voltage was 1 V, the low voltage was -1 V, the starting voltage was the open circuit voltage, the scan rate was 0.01 V / S, and the scan time was 600 S;

[0057] Step 4. After electroplating, take out the carbon paper, rinse it with deionized water for 1 minute, and then put it into a drying oven at 60°C for 12 hours.

[0058] Example 4

[0059] A method for preparing a lithium-sulfur battery positive electrode composite current collector comprises the following steps:

[0060] Step 1. Select hydrophilic carbon paper and pre-treat it: Use scissors to cut the hydrophilic carbon paper into squares (2×2cm 2 ), then ultrasonically cleaned with alcohol and deionized water for 20 min respectively to remove surface oil and dust, and then placed in a drying oven at 60 ° C for 12 h;

[0061] Step 2. Prepare hydrogen molybdenum bronze electroplating solution: 196 mg of ammonium molybdate ((NH4)6Mo7O 24 ) was dissolved in 100 mL of deionized water and stirred for 2 h to obtain an ammonium molybdate solution; concentrated sulfuric acid (H2SO4) was slowly added dropwise to the ammonium molybdate solution, the pH value of the solution was adjusted to 2.7, and stirred for 30 min to obtain a hydrogen-molybdenum bronze electroplating solution;

[0062] Step 3. Electroplating hydrogen molybdenum bronze, specifically:

[0063] Take 30 ml of the hydrogen molybdenum bronze electroplating solution obtained in step 2 into a 50 ml electrolytic cell, use the carbon paper pretreated in step 1 as the working electrode, and a Pt sheet (2×2 cm 2 ) was used as the counter electrode, and the calomel electrode was used as the reference electrode. The electrodeposition was carried out by cyclic voltammetry at room temperature using a CHI660 electrochemical station with a standard three-electrode structure; the working parameters of the cyclic voltammetry were as follows: the high voltage was 1 V, the low voltage was -1 V, the starting voltage was the open circuit voltage, the scan rate was 0.01 V / S, and the scan time was 600 S;

[0064] Step 4. After electroplating, take out the carbon paper, rinse it with deionized water for 1 minute, and then put it into a drying oven at 60°C for 12 hours.

[0065] Comparative Example 1

[0066] A method for preparing a lithium-sulfur battery positive electrode composite current collector comprises the following steps:

[0067] Step 1. Select hydrophilic carbon paper and pre-treat it: Use scissors to cut the hydrophilic carbon paper into squares (2×2cm 2 ), then ultrasonically cleaned with alcohol and deionized water for 20 min respectively to remove surface oil and dust, and then placed in a drying oven at 60 ° C for 12 h;

[0068] Step 2. Slowly add concentrated sulfuric acid (H2SO4) to deionized water to adjust the pH to 3 and stir for 30 minutes. Soak the pretreated carbon paper in the acidic solution for 1 hour, rinse with deionized water for 1 minute, and then put it in a drying oven at 140°C for 12 hours to obtain the positive electrode current collector of the lithium-sulfur battery.

[0069] The positive electrode current collectors obtained in Example 1, Example 2 and Comparative Example 1 were respectively assembled into lithium-sulfur batteries: containing 1MLi TFSI and 2wt% LiNO3 as lithium salts, and a DME:DOL solution with a volume ratio of 1:1 as the electrolyte of the lithium-sulfur battery. The sulfur loading of the assembled full battery was 1mg / cm 2 . The specific assembly process is: S powder and ECP600 JD are mixed in a mass ratio of 8:2, and hydrothermally treated at 155°C for 10 hours to form a sulfur / carbon composite material. First, the sulfur / carbon composite material is mixed with a 5wt% PVDF solution (NMP as solvent) for 1 minute, then NMP is added to adjust the viscosity, and then mixed for another 9 minutes to prepare a cathode slurry. The mass ratio of sulfur / carbon composite material to PVDF in the mixed solution is 10:1.5. All cathodes were prepared by drop-coating the slurry onto hydrogen-molybdenum bronze-coated carbon paper, and first dried in an oven at 65°C for 30 minutes to remove most of the solvent. Subsequently, it was transferred to a vacuum oven set at 50°C and left overnight for further drying. The Li-S battery is composed of a negative electrode shell, a lithium sheet, a 30μL electrolyte, a PP separator, a 30μL electrolyte, a sulfur positive electrode (approximately equal to 1mg·cm -2 ), stainless steel sheet, spring, positive electrode shell. Finally, the stacked batteries are sealed with a hydraulic sealing machine with a sealing pressure of 500psi.

[0070] Comparative Example 2

[0071] A method for preparing a lithium-sulfur battery positive electrode composite current collector comprises the following steps:

[0072] Step 1. Select hydrophilic carbon paper and pre-treat it: Use scissors to cut the hydrophilic carbon paper into squares (2*2cm 2 ), then ultrasonically cleaned with alcohol and deionized water for 20 min respectively to remove surface oil and dust, and then placed in a drying oven at 60 ° C for 12 h;

[0073] Step 2. Prepare hydrogen molybdenum bronze electroplating solution: 196 mg of ammonium molybdate ((NH4)6Mo7O 24 ) was dissolved in 100 mL of deionized water and stirred for 2 h to obtain an ammonium molybdate solution; concentrated sulfuric acid (H2SO4) was slowly added dropwise to the ammonium molybdate solution, the pH value of the solution was adjusted to 3, and stirred for 30 min to obtain a hydrogen-molybdenum bronze electroplating solution;

[0074] Step 3. Electroplating hydrogen molybdenum bronze, specifically:

[0075] Take 30 ml of the hydrogen molybdenum bronze electroplating solution obtained in step 2 into a 50 ml electrolytic cell, use the carbon paper pretreated in step 1 as the working electrode, and a Pt sheet (2×2 cm 2) was used as the counter electrode and calomel electrode as the reference electrode, and the electrodeposition was carried out by cyclic voltammetry at room temperature using a CHI660 electrochemical station with a standard three-electrode structure; the working parameters of the cyclic voltammetry were as follows: the high voltage was 0.8 V, the low voltage was -0.8 V, the starting voltage was the open circuit voltage, the scan rate was 0.1 V / S, and the scan time was 600 S.

[0076] The test results of the changes of the discharge specific capacity and coulombic efficiency of the lithium-sulfur batteries prepared in Example 1, Comparative Example 1 and Example 2 with the number of cycles at a rate of 0.5C are as follows: Figure 3 to Figure 5 As shown. Figure 3 to Figure 5 It can be seen that compared with Comparative Example 1, the capacity of the lithium-sulfur battery after the positive electrode composite current collector materials of Examples 1 and 2 were loaded with hydrogen-molybdenum-bronze increased from 261mah·g to 261mah·g after 400 cycles. -1 Increased to 444mah·g -1 and 515mah·g -1 , indicating that the composite current collector of the present invention can inhibit the shuttle effect, and the lithium-sulfur battery prepared based on the current collector has better cycle performance and higher charge-discharge specific capacity.

[0077] Figure 6 This is the EDS graph of the Mo element in the composite current collector material obtained in Comparative Example 2 of the present invention. As can be seen from the figure, after electroplating, it was found that the hydrogen-molybdenum bronze dissolved in water did not adhere to the surface of the carbon fiber to form a coating, and the EDS spectrum of the Mo element also showed that there was only a very small amount of Mo element on the carbon fiber, indicating that the electroplating of the hydrogen-molybdenum bronze coating on the carbon paper was not successful.

[0078] The above description is only a specific implementation mode of the present invention. Any feature disclosed in this specification, unless otherwise stated, can be replaced by other alternative features that are equivalent or have similar purposes; all the disclosed features, or all the steps in the methods or processes, except for mutually exclusive features and / or steps, can be combined in any way.

Claims

1. A lithium-sulfur battery positive electrode composite current collector, characterized in that: The invention comprises a positive electrode current collector and a hydrogen-molybdenum-bronze coating attached to the surface of the positive electrode current collector; the hydrogen-molybdenum-bronze coating is electroplated on the surface of the positive electrode current collector by using a cyclic voltammetry method.

2. The lithium-sulfur battery positive electrode composite current collector according to claim 1, characterized in that: The positive electrode current collector is a hydrophilic current collector.

3. A method for preparing a composite current collector for a lithium-sulfur battery cathode, characterized in that: The following steps are involved: Step 1. Cleaning the positive electrode current collector and then drying it; Step 2. Prepare hydrogen molybdenum bronze electroplating solution: Add ammonium molybdate ((NH4)6Mo7O 24 ) is dissolved in deionized water and stirred to obtain an ammonium molybdate solution; then concentrated sulfuric acid is added dropwise to the ammonium molybdate solution to adjust the pH value of the solution and stir for a period of time to obtain a hydrogen-molybdenum bronze electroplating solution; Step 3. Electroplating hydrogen molybdenum bronze, specifically: Using an electrochemical workstation three-electrode system, the positive electrode current collector dried in step 1 was used as the working electrode, Pt was used as the counter electrode, and the calomel electrode was used as the reference electrode. Hydrogen molybdenum bronze was electroplated on the positive electrode current collector by cyclic voltammetry at room temperature; Step 4. After the electroplating is completed, the positive electrode current collector is taken out, cleaned and dried to obtain the desired lithium-sulfur battery positive electrode composite current collector.

4. The preparation method according to claim 3, characterized in that: In step 1, the positive electrode current collector is a hydrophilic current collector, and the hydrophilic current collector is a hydrophilic carbon paper or a hydrophilic carbon cloth.

5. The preparation method according to claim 4, characterized in that: The hydrophilic current collector is a hydrophilic current collector or a hydrophobic current collector obtained after being treated to be hydrophilic.

6. The preparation method according to claim 5, characterized in that: The specific process of hydrophilic treatment of the hydrophobic current collector is as follows: The hydrophobic current collector is firstly ultrasonically cleaned and dried, and then immersed in nitric acid for hydrophilic treatment; after the hydrophilic treatment, it is ultrasonically cleaned and dried again.

7. The preparation method according to claim 3, characterized in that: The concentration of ammonium molybdate in deionized water is 0.05-1 mmol / L.

8. The preparation method according to claim 3, characterized in that: The pH value of the solution after the addition of concentrated sulfuric acid is 2.7-3.

9. The preparation method according to claim 3, characterized in that: The specific parameters of the cyclic voltammetry method are: the high voltage is 1V, the low voltage is -1V, the starting voltage is the open circuit voltage, the scanning rate does not exceed 0.05V / S, and the scanning time is 200S-600S.

10. An application of a lithium-sulfur battery positive electrode composite current collector prepared by the preparation method according to any one of claims 3 to 9 in a lithium-sulfur battery, characterized in that: Specifically, sulfur is loaded on the positive electrode composite current collector to obtain a sulfur positive electrode. Place the negative electrode shell, lithium sheet, electrolyte, diaphragm, electrolyte, sulfur positive electrode, stainless steel sheet, shrapnel and positive electrode shell in order from bottom to top. Finally, the stacked batteries are sealed with a hydraulic sealing machine to obtain the desired lithium-sulfur battery.